Post-recurrence survival analysis of patients with pulmonary recurrence from gynaecologic cancers: a multi-institutional analysis of 122 patients. (3rd October 2022) - Ersak, Burak; Akar, Serra; Demirayak, Gökhan; Tokalioğlu, Abdurrahman Alp; Aytekin, Okan; Çakir, Caner; Yüksel, Dilek; Tokgözoğlu, Nedim; Karakaş, Sema; Önder, Ayşe Büşra; Çelik, Fatih; Ayhan, Sevgi; et al.
Abstract: In this retrospective study, patients with epithelial gynaecologic cancer with pulmonary recurrence (PR) were evaluated from five national gynaecologic oncology clinics. Patients with a diagnosis of primary endometrial, ovarian/fallopian tube/peritoneal, cervical or vaginal/vulvar tumours who developed an initial PR were included in the study A total of 122 patients were included in the study. The median follow-up time after recurrence was 7.5 (range, 1–84) months. The 2-year PRS was 48% in the main cohort. The risk of death was more than seven times higher in patients who did not receive salvage chemotherapy compared with those who did (hazard ratio: 7.6, 95% CI: 3.0–18.9; p <  .001). When squamous cell carcinoma was compared with the other tumour types, the risk of death increased more than three times (hazard ratio: 3.7, 95% CI: 1.4–9.6; p  = .007). IMPACT STATEMENT: What is already known on this subject? Pulmonary recurrence (PR) from gynaecologic malignancies is rare and can cause major clinical problem. Therefore, defining the clinical and pathologic characteristics and recurrence patterns are essential. What the results of this study add? This study demonstrates non-squamous subtype and salvage chemotherapy at PR were associated with improved survival. What of these findings for clinical practice and/or further research? To the best of our knowledge, our study is the largest study to investigate the clinico-pathologic characteristics, recurrence patterns, treatment options, and post-recurrence survival (PRS) in patients with PR from epithelial gynaecologic cancers. Future research should examine the underlying causes of these findings.